Gross Anatomy and Histological Features of Gymnarchus niloticus (Cuvier, 1829) from the River Niger at Agenebode in Edo State, Nigeria - Agbugui, M. O.; Abhulimen, F. E.; Egbo, H. O. (International Journal of Zoology, 2021)
This study was conducted to record the anatomy and histological features of the gastrointestinal tract of the trunk fish Gymnarchus niloticus captured at Agenebode in the Lower River Niger, Edo State. The gastrointestinal tract was segmented into the mouth, oesophagus, stomach, pyloric caeca, and intestine. The slender (taeniform) body that is fuller at the head tappers at its end. There are no spines on this fish, and the fins used for locomotion are the dorsal fins and not the typical pectoral fins as in other fish. The oesophagus, stomach, pyloric caeca, intestine, and cloaca (anterior, intermediate, posterior, and rectum) were analysed for histological examination. The stomach had significantly higher villi and thicker inner circular muscles compared to the intestine and oesophagus. The lamina propria was thickest in the stomach which is significantly higher when compared with the oesophagus, but not with the intestine. However, the intestine showed significantly thicker outer longitudinal muscle, while gastric glands were observed only in the stomach. The histological features were closely associated with the functions of the different segments of the gastrointestinal tract. In conclusion, the histological features of the gastrointestinal tract of G. niloticus are consistent with the feeding habit of a carnivorous fish. In conclusion, the GIT is a complex structure composed of organs that reveals that it is a higher vertebrate created for a hardy survival, consistent with the feeding habit of a carnivorous fish. The histology reveals a GIT formed by four conspicuous layers from the inside to the outside of the mucosa, submucosa, and an inner longitudinal layer of the muscularis and the outer circular of the muscularis typical of higher vertebrates.